CYBERBULLYING IN MOVIE CYBERBULLY: AN ANALYSIS FROM THE PSYCHOLOGICAL PERSPECTIVE - Nine Febrie Novitasari; Nadya Irma Aggriny Hia (University of Muhammadiyah Malang, 2021)
The development of technology, including Internet, has raised the number of cyberbullying. Social media is on where cyberbullying commonly occurs as most of its users are teenagers. This current research tried to analyse the phenomena of cyberbullying on a movie entitled Cyberbully. This movie is centered to the main character, Casey, whose computer got hacked, and she got bullied by an anonymous hacker. The objectives of this research were to find the types of cyberbullying the main character suffered from, and the effects of cyberbullying the main character experienced. The results show the types of cyberbullying appearing in the movie are harassment, denigration, impersonation, outing and trickery, and cyberstalking with the latter dominating. Meanwhile, the effects of cyberbullying found were increased emotional distress, lowered self-esteem, isolation and withdrawal, and indulging in harmful habits with isolation withdrawal as the most dominant one. From the results, it can be concluded that how someone’s id, ego, and superego work is related to the defense mechanism performed. In this movie, the main character shows her dominant personality sistem, that is super ego as she made decisions based on morals and judgements about right and wrong, and her decisions were based more on moral values. Besides, people who are active in social media can provoke cyberbullying. The effects are very dangerous because they can damage the victim's mentality and even makes the victim a potential perpetrator. This actually is a warning for young people to see. Thus, the wise use of social media is advisable.